“Bundle of Sticks” and the Value of Interdependence: Building a Tools and Services Collective - Katherine Elizabeth Skinner (Journal of Electronic Publishing)
In this article, we raise questions about how bundling and independence show up in the scholarly publishing industry today, both for large conglomerates and for smaller commercial and nonprofit players. We then contemplate what interdependence might look like and how it might help to transform academic publishing. We end with findings from the Next Generation Library Publishing (NGLP) project (2019-2022) and its Collaborative Frameworks Working Group regarding a set of initial steps that we believe publishers, tools, and service providers might take together towards developing a collective publishing framework for open source, values-aligned tools and services.